Protective effect of flavonoid and saponin-rich fractions against renal toxicity induced by mercuric chloride in rodent model - LADUMOR, VIPUL C; MODI, CHIRAG M; S, SHREESHA RAO; PATEL, URVESH D; PATEL, HARSHAD B; MAKWANA, CHANDRASINH N (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to evaluate the ameliorating potential of the flavonoid-rich fraction of Phyllanthus emblica (FRFPE) and saponin-rich fraction of Tribulus terrestris (SRFTT) against mercuric chloride (HgCl2)-induced renal toxicity in rats. Forty-two male SD rats were divided into seven different groups, namely normal control (C1), toxicity control (C2), vehicle control (C3), standard control (C4), Flavonoid rich fraction of Phyllanthus emblica (FRFPE; T1), Saponin rich fraction of Tribulus terrestris (SRFTT; T2) and FRFPE + SRFTT (T3). Serum biochemical markers and oxidative stress indicators were measured. Histopathological examination of kidney sections was also carried out. Our data revealed that BUN and creatinine levels in rats’ serum were significantly higher, whereas serum total protein, albumin, and globulin levels were significantly lower in the toxicity group. HgCl2 administration reduced the activity of superoxide dismutase (SOD), catalase (CAT) and reduced glutathione (GSH) and an elevated MDA in kidney tissue when compared with the control. The treatment with FRFPE and SRFTT markedly attenuated HgCl2-induced oxidative stress in kidney. Further, oxidative stress-related alteration in biochemical markers was confirmed by histopathological changes in rats of different treatment groups. According to histopathology of the kidney, the treatment of FRFPE and SRFTT considerably reduced the damage produced by HgCl2 in rats. LC-QTOF-MS analysis of FRFPE and SRFTT showed the presence of tannins, triterpenoids, alkaloids, gallic acid, steroid derivatives, quinoline derivatives and flavonoids. According to the findings, the flavonoid-rich fraction of P. emblica and the saponin-rich fraction of T. terrestris showed an antioxidant activity and protected the rat kidney from mercury-induced oxidative damage.